Estimation degree possible defeat of the combat wheel machine crew members depending on place of his location in the event undermining on mine - Pisarev, V. P. (Honor and Law, 2019)
The mathematical model of the estimation defeat of the crew members is offered in the event of undermining on mine. With use the numerical methods are organized calculations, concerning degree defeat of the person on place of his location depending on distances him before place of the undermining